2012
DOI: 10.1115/1.4007318
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Analysis of Indirect Combustion Noise in Subcritical Nozzles

Abstract: This article revisits the problem of indirect combustion noise in nozzles of finite length. The analytical model proposed by Moase for indirect combustion noise is rederived and applied to subcritical nozzles having shapes of increasing complexity. This model is based on the equations formulated by Marble and Candel for which an explicit solution is obtained in the subsonic framework. The discretization of the nozzle into n elementary units of finite length implies the determination of 2n integration constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…For an axisymmetric configuration, Leyko et al [16] using the compact nozzle approximation of Marble & Candel [6] and considering reflection from EWG rig outlet found excellent agreement between their analytical solution and experimental measurements. In addition to the choked isentropic nozzle studied by Leyko et al [16] a subsonic configuration has been studied by Giauque et al [25] and Duràn et al [34]. The analytical results of Duràn et al [34] based on a compact nozzle hypothesis for unchoked subsonic nozzle showed that the strength of the indirect noise is two orders of magnitude smaller than the direct noise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For an axisymmetric configuration, Leyko et al [16] using the compact nozzle approximation of Marble & Candel [6] and considering reflection from EWG rig outlet found excellent agreement between their analytical solution and experimental measurements. In addition to the choked isentropic nozzle studied by Leyko et al [16] a subsonic configuration has been studied by Giauque et al [25] and Duràn et al [34]. The analytical results of Duràn et al [34] based on a compact nozzle hypothesis for unchoked subsonic nozzle showed that the strength of the indirect noise is two orders of magnitude smaller than the direct noise.…”
Section: Introductionmentioning
confidence: 99%
“…The compact solution of Marble & Candel [6] has been extended to non-compact nozzles in the linear regime for choked nozzles with a shock [18,22,23], or with an isentropic supersonic expansion [24], and for subcritical nozzles [25]. Stow et al [18] and Goh & Morgans [22] used an asymptotic expansion of the linearized Euler equations to show that slightly non-compact nozzles can be modelled through use of an effective nozzle length that is slightly longer than the physical length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer functions of the realistic nozzle geometry calculated with the Magnus expansion are also compared with a numerical solver (Silva 2010;Giauque et al 2012), solving the linearized Euler equations in the frequency domain with a second order centred spatial scheme. The discretization is such as to have at least 100 points per acoustic wavelength for Ω = 5 at the inlet.…”
Section: Comparison With a Linear Steady Velocity Choked Nozzlementioning
confidence: 99%
“…Direct and indirect noise in a reflective environment 437 Giauque, Huet & Cléro 2012;Durán, Moreau & Poinsot 2013;Lourier et al 2014). In the case where the nozzle is operated in the supersonic regime, Leyko et al (2011) indicated that the measured pressure signal was primarily due to indirect noise.…”
mentioning
confidence: 99%